2015
DOI: 10.1055/s-0034-1398742
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Antimicrobial Therapy of Sepsis and Septic Shock: Focus on Antibiotic Combination Therapy

Abstract: Severe sepsis and septic shock with sepsis-associated multiple organ failure represent the major causes of infection-associated mortality and remain the most common cause of death in intensive care units (ICUs) of developed countries. They account for 10 to 15% of all ICU admissions and 25% of sepsis cases 1 ; up to 50 to 75% of severe sepsis cases progress to septic shock. 2 Septic shock alone represents 5 to 8% of all ICU admissions. 3 Historically, the mortality associated with sepsis and septic shock has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
13

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 147 publications
(164 reference statements)
0
38
0
13
Order By: Relevance
“…Studies by Kumar et al (39,40) found that rapid and early antibiotic treatment significantly increases survival in an immunocompetent murine infection model of septic shock. These studies and our simulations suggest that a continuous infusion of imipenem at 5 g/day (with a loading dose) plus tobramycin at 7 mg/kg every 24 h may provide a beneficial effect in reducing the bacterial burden to an extent where the immune system in immunocompetent patients can achieve bacterial clearance.…”
Section: Yadav Et Al Antimicrobial Agents and Chemotherapymentioning
confidence: 99%
“…Studies by Kumar et al (39,40) found that rapid and early antibiotic treatment significantly increases survival in an immunocompetent murine infection model of septic shock. These studies and our simulations suggest that a continuous infusion of imipenem at 5 g/day (with a loading dose) plus tobramycin at 7 mg/kg every 24 h may provide a beneficial effect in reducing the bacterial burden to an extent where the immune system in immunocompetent patients can achieve bacterial clearance.…”
Section: Yadav Et Al Antimicrobial Agents and Chemotherapymentioning
confidence: 99%
“…7 It remains controversial if combination antimicrobial therapy produces a better outcome than adequate single-agent antibiotic therapy in patients with sepsis. [53][54][55] One major retrospective analysis of sepsis showed an increased mortality of 7.6% for each hour of delay in the administration of appropriate antibiotic. 6 Despite extensive research in the last few decades to define sepsis and to improve the outcome of patients, it remains a challenge to identify the better therapeutic approach for clinical management and for survival of subjects.…”
Section: Therapeutic Interventionsmentioning
confidence: 99%
“…However, the timeliness of appropriate therapeutic management influences the prognosis in sepsis (3). Early recognition of infectious source and early initiation of appropriate empiric antimicrobial therapy with source control is crucial for decreasing the risk of organ failure (5). The Surviving Sepsis Campaign suggested two "bundles" of care to improve outcome in sepsis and septic shock; initial management bundle in emergency department within 6 hours and accomplished management bundle in intensive care units (ICU) (6).…”
Section: Appropriate Empiric Antimicrobial Therapymentioning
confidence: 99%
“…For these antibiotics, the key PK parameter for maximum efficacy is the time that serum levels above the minimal inhibitory concentration (MIC) of the pathogen. Continuous or prolonged infusion is suggested to have the optimal efficacy (improved clinical cure, shorter hospitalization and lower mortality) from beta lactams, carbapenems and linezolid (5,30). Whereas, fluoroquinolones, aminoglycosides, colistin and vancomycin are concentrationdependent antibiotics and high peak drug concentrations are needed for maximal efficacy (5,30).…”
Section: Pharmacokinetics (Pk)/pharmacodynamics (Pd) Of Antibioticsmentioning
confidence: 99%
See 1 more Smart Citation